OPTICAL THEORY OF AXONOMETRIES, USED IN THE HISTORY OF CENTRAL ASIAN PAINTING - Sh. Abdurahmanov; S. Rahmatullaev; S. Yoldoshev (Galaxy International Interdisciplinary Research Journal, 2022)
The article, named as "The optical theory of axonometry applied in the history of drawing in Central Asia", comprehensively presents scientific information about axonometry, about their theory applied by artists in the history of Central Asia of the IX – XIX centuries.